Regulation of Law of the Republic of Indonesia Number 17 of 2023 on Control of Catastropic Diseases Linked to Financing of National Health Insurance Based on Dignified Justice - Permatasari, Resti; Prasetyo, Teguh; Jaeni, A (PSPP JOURNALS, 2024)
This study aims to analyze the provisions in Law of the Republic of Indonesia Number 17 of 2023 concerning Catastrophic Disease Control, especially related to the financing of the National Health Insurance (JKN) based on the principle of dignified justice. This study uses a normative legal method with a legislative and comparative approach, as well as descriptive-analytical specifications. The analysis was carried out by examining related regulations, government responsibilities, and comparative studies with other countries such as the United States, England, Canada, and Australia. The results of the study indicate several challenges in the implementation of catastrophic disease control in Indonesia, especially in financing through JKN. Although Law Number 17 of 2023 has provided a comprehensive legal framework, there are gaps in the efficient use of JKN funds and disparities in access to health services between urban and rural areas. In addition, this study also found that the role of the government as a regulator and service provider creates potential conflicts of interest. Based on the legal analysis conducted, policy recommendations are proposed to improve the regulation and implementation of catastrophic disease control through improving institutional structures, increasing financing transparency, and strengthening the role of government in ensuring fair and quality access.